Postcolonial India: History, politics and culture - Damodaran, Vinita; Unnitha-Kumar, Maya (New Delhi Manohar, 2000)
The book surveys and analyzes the economic, political and cultural changes which have taken place in India since its independence. Includes 17 essays by younger Indian scholars and a few western specialists, presented at a 1997 Sussex conference, on Gadhi, literature, dalits, Hyderabad, poverty, economics, women, and a final section on the arts including art, cinema, architecutre and post-colonial issues. It provides dynamic new insights into the half-century since independence.